Copper(II) and Nickel (II) Complexation Capacity of Dissolved Organic Matter from Rivers of Agricultural and Urban Areas in the State of Sao Paulo - Tadini, Amanda M. [UNESP]; Campanha, Mariele B. [UNESP]; Moreira, Altair B. [UNESP]; Bisinoti, Marcia C. [UNESP] (Soc Brasileira Quimica, 2013)
This study had as main objective to determine the complexing ability of the Organic Matter (OM) from typical agricultural areas and from urban areas with copper and nickel ions. The samples were collected during the dry and rainy seasons and were subjected to study the complexing capacity and OM conditional stability constant with Cu(II) and Ni(II) ions using a luminescence spectrofluorometer and tangential flow ultrafiltration system. The conditional stability constant values (log K-c) of OM with the copper ion varied from 0.04 to 1.35 with the highest value obtained for the place with the largest dissolved organic carbon (DOC 2.73-2.43 mg L-1) and the lowest for the smallest site DOC, corroborating the degree of aromaticity. We can conclude that the Dissolved Organic Matter (DOM) of the bodies of water in agricultural and urban areas contained a lower number of binding sites when compared with other locations.
Keywords: dissolved organic matter; Metals; stability constant